Cathedrals, Laudianism, and the British Churches - Atherton, Ian (The historical journal, 2010)
Recent research has argued that English cathedrals, particularly but not exclusively Westminster Abbey, formed a ‘liturgical fifth column’ in the church and were the Trojan horse by which Laudianism – the ceremonial, clericalist, anti-Calvinist policies associated with Charles I and William Laud in the 1620s and 1630s – was introduced into the English church. This article re-examines links between cathedrals and Laudianism, not just in England, but also in the associated Protestant state churches of Charles's other realms: Ireland and Scotland. Laudian divines emphasized cathedrals as liturgical showcases, ‘mother churches’ which their ‘daughters’, the parish churches, should follow in the policy of the ‘beauty of holiness’, particularly the placing, railing of, and reverence to the Laudian altar. However, cathedrals are shown to be more diverse than historians have generally allowed, and Laudian policies are shown to have been grafted on to cathedrals, rather than emerging from them. Caroline cathedrals were more the victims of Laudianism than its midwives.